Food insecurity questionnaire on knowledge, attitudes, and practices for perinatal care professionals - Gabriela Buccini; Ambree Schoetker; Ana Poblacion; Smriti Neupane; Timothy J. Grigsby; Dodds Simangan; Jyoti Desai; Allison Brown; Juanita Chinn; Manoj Sharma (PLoS ONE, 2025)
Background Perinatal care professionals are presented with regular opportunities to screen for food insecurity risk and provide referrals for their patients. However, their own experience or lack thereof with food insecurity may interfere with the implementation of screening. Thus, we aimed to develop, validate, and pilot a food insecurity knowledge, attitudes, and practices questionnaire (KAP-FI) for perinatal care professionals that can support the implementation of universal screening for food insecurity. Method A multi-step process included (a) questionnaire development, (b) content validation, (c) face validation, (d) reliability and readability, and (e) pilot assessment of KAP-FI. The research team developed the questionnaire; five experts in maternal-child health assisted with content validity, and eight perinatal care professionals assisted with face validity and readability. The pilot phase was carried out with seventy-two perinatal care professionals providing direct services to pregnant people or children under three years in Clark County, Nevada, United States. Results KAP-FI included 53 items after content validation, face validation, and pilot phases. Responses from the pilot showed that about 60% of professionals (n = 42) are aware of the 2-item food insecurity screening tool (Hunger Vital Sign™), but of that half (n = 23) indicated that universal screening for food insecurity may not be beneficial to clients/patients. Nonetheless, professionals shared that food insecurity screening (n = 62, 86.1%), referral (n = 69, 95.8%), and follow-up (n = 71, 98.6%) would increase patients trust in them. Thus, 40% (n = 29) reported using a checklist or other reminders to prompt them to screen their clients/patients for food insecurity risk. Conclusions KAP-FI is an appropriate and feasible tool to identify baseline barriers and facilitators on knowledge, attitudes, and practices of perinatal care professionals to address food insecurity in the United States.